Providing fairness and effectiveness reasoning for obesity policies increases policy support - Lucie Martin; Maria Lee; Deirdre Robertson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2025)
This study investigates how providing fairness and effectiveness reasoning for obesity prevention policies impacts support for these policies. We used an online experimental survey to measure support for 12 policies. 1,353 participants were randomly shown a control version (basic description), a version with an effectiveness reasoning, or a version with a fairness reasoning for each policy. Policy support was high. Effectiveness and fairness treatments modestly increased support. Among fairness treatments, those about autonomy (respecting freedom of choice) were most effective. Effects varied by policy and treatment and did not depend on individual-level factors (e.g., attitudes).
Keywords: 330; Obesity; Overweight; Obesogenic; Policy; Perceptions; Fairness; Effectiveness; Environment